Spiritual Emotional Freedom Technique for Enhancing the Meaning of Life in Patients with Ischemic Stroke - Dedek Saiful Kohir; Agilia Nur Fauziah; Sulastri Sulastri; Almurhan Almurhan; Sunarsih Sunarsih; Siti Fatonah (Jurnal Kesehatan, 2026)
Beyond its effects on physical motor abilities, ischemic stroke frequently results in psychological and spiritual crises. Loss of "meaning in life," a commonly disregarded effect, can seriously impair a patient's motivation throughout long-term recovery. Psychospiritual therapies, such as the Spiritual Emotional Freedom Technique (SEFT), which combines spiritual affirmations with meridian-tapping procedures, are used to address this. The purpose of this study is to examine how SEFT treatment affects ischemic stroke patients' sense of purpose in life in a clinical environment. This study used a one-group pretest-posttest methodology and a quantitative pre-experimental design. All stroke patients at RSUD (Regional public hospital) Jenderal Ahmad Yani made up the population. A purposive sampling method was used to select 39 eligible respondents: individuals aged 20 to 60 who were willing to participate in the Spiritual Emotional Freedom Technique (SEFT). They were also of sound mind (compos mentis). The intervention included two SEFT therapy sessions, which took place over two weeks. To measure the differences before and after the intervention, the Meaning in Life Questionnaire (MLQ) was used for data collection, and the Paired Sample T-Test was used for data analysis. The results showed that the "meaning in life" ratings significantly increased after the SEFT intervention, with a significance value of 0.001 (p < 0.05). Patients said they felt more at ease, accepted their status better, and had more optimism for the future. By releasing negative emotions and bolstering spiritual resilience, SEFT is successful in assisting ischemic stroke patients in regaining their sense of purpose. To enhance holistic and humanistic healthcare services, this intervention is advised as a crucial component of psychospiritual nursing care. In addition to standard physical therapy, nurses are urged to educate patients and their families on this self-help method.